1998
DOI: 10.1148/radiology.207.2.9577479
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MR imaging of bone marrow: differentiation of benign versus pathologic compression fractures.

Abstract: Diffusion-weighted MR imaging provided excellent distinction between pathologic and benign vertebral compression fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
198
1
13

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(214 citation statements)
references
References 0 publications
2
198
1
13
Order By: Relevance
“…In a study of benign and pathologic spinal compression fractures using SSFP DWI, Baur et al [25] reported that all malignant compression fractures were hyperintense to normal marrow, whereas most benign compression fractures were hypointense to normal marrow. However, a subsequent study by Castillo et al [26] showed no advantage of DWI in the detection and characterization of vertebral metastases compared with T1-weighted imaging; metastases were hypointense to normal marrow in 3 out of 5 patients with focal disease and 5 out of 10 patients with multiple lesions.…”
Section: Fat and Water Contentmentioning
confidence: 99%
“…In a study of benign and pathologic spinal compression fractures using SSFP DWI, Baur et al [25] reported that all malignant compression fractures were hyperintense to normal marrow, whereas most benign compression fractures were hypointense to normal marrow. However, a subsequent study by Castillo et al [26] showed no advantage of DWI in the detection and characterization of vertebral metastases compared with T1-weighted imaging; metastases were hypointense to normal marrow in 3 out of 5 patients with focal disease and 5 out of 10 patients with multiple lesions.…”
Section: Fat and Water Contentmentioning
confidence: 99%
“…MR sequences such as T1WI and CE-FS T1WI are valuable for the assessment of cranial bone marrow because they have high spatial resolution and tissue contrast. DW-MRI has been applied to vertebral bodies to differentiate between benign and malignant vertebral compression fractures 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, all patients underwent in-house MRI (T1-weighted sequence ± contrast, short tau inversion recovery sequence, axial and sagittal orientation) prior to vertebroplasty to assess the pattern of bone marrow involvement and vertebral and paravertebral tumor involvement and to detect the level(s) of vertebral edema in cases of multiple VCFs detected on CT (18).…”
Section: Imaging Workup and Guidancementioning
confidence: 99%